TUJUAN PENDIDIKAN ROHANI DALAM PERSPEKTIF PENDIDIKAN SUFISTIK - Akmansyah, M (Universitas Islam Negeri Raden Intan Lampung, 2016)
The Islamic education has two dimensions: toacquire intellectual knowledge (through theapplication of logic and reasoning) and developspiritual knowledge (gained from divine revelationand spiritual experiences). God is the centre andfocus of education; hence to be educated aMuslim means to be devoted to attaining thepleasure of God. This should result in piousactions that would enable the Muslim to drawcloser to God. The aim of education is thecreation of the good and righteous man whoworships Allah in the true sense of the term,builds up the structure of his earthly life accordingto the Syaria and employs it to subserve his faith.The purpose of spiritual education is expected tofind, nurture and develop individual relationshipsverticalharmonious; until (wushūl) to God withfidelity to Him alone, implementing Islamicmorality exemplified by the Prophet based on theideals of the Qur’an.